2010
DOI: 10.1007/s12031-010-9412-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Expression of Apolipoprotein E in Mouse Cerebral Cortex

Abstract: Apolipoprotein E (apoE) is predominantly a lipid transport protein involved in membrane repair and synaptic plasticity in brain. Its genotype is associated with late-onset sporadic and familial Alzheimer's disease (AD). Its expression increases when any injury takes place in the nervous system and in age-related disorders including AD. However, it is not clearly understood how the level of apoE changes in the normal aging brain. Therefore, we have analyzed the effect of age on apoE protein and mRNA level in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In this study the density levels of APOE-positive capillaries are slightly elevated in AD cases relative to those found in CG cases. A recent study in mice indicates that in the normal aging brain in mice APOE levels remain constant as a function of age [35]. There is no reported human study regarding this issue.…”
Section: Discussionmentioning
confidence: 98%
“…In this study the density levels of APOE-positive capillaries are slightly elevated in AD cases relative to those found in CG cases. A recent study in mice indicates that in the normal aging brain in mice APOE levels remain constant as a function of age [35]. There is no reported human study regarding this issue.…”
Section: Discussionmentioning
confidence: 98%
“…We reported that ApoE expression decreased from young to adult and then remained unchanged in old mouse cerebral cortex. Certainly, such expression profile suggested the involvement of other factors in maintaining ApoE level and dependent brain functions in old [ 28 ].…”
Section: Ad Associated Genesmentioning
confidence: 99%
“…Also, some studies have shown that there is no age-related alteration in apoE protein level (Gee et al 2006;Ramaswamy et al 2005). Recently, our own study has shown that there is no age-related alteration in apoE level in adult and old male mice (Singh and Thakur 2010). So if there is no difference in apoE level due to age, it is likely that sex hormones have no effect on it.…”
Section: Western Blot Analysis Of Apoe In Gonadectomized and Hormone-mentioning
confidence: 91%